The Mughals and the Sufis : Islam and political imagination in India, 1500-1750 - Alam, Muzaffar, 1947- (Albany : State University of New York Press, 2021)
"Examines the relationship between Mughal political culture and the two dominant strains of Islam's Sufi traditions in South Asia: one centred around orthodoxy, the other focusing on a more accommodating and mystical spirituality"--
Introduction: A long view of Sufism and political culture in India -- The Mughals, the Sufi Shaikhs, and the formation of the Akbari dispensation -- A Sufi critique of religious law, tasawwuf, and politics in Mughal India -- Shah Madar, Sufi religion, and a view of "true Islam" in a Mughal Chishti Tazkira -- Strategy and imagination in a Mughal Sufi story of creation -- In search of a sacred king : Dara Shukoh and the Yogavasisthas of Mughal India -- Piety, poetry, and the contested loyalties of Mughal princesses, c. 1635-1700 -- The Naqshbandi Shaikhs of Sirhind in Aurangzeb's empire and its aftermath.
Includes bibliographical references and index.
JSTOR
Keywords: Sufism -- India -- History; Islam and politics -- India; Islam and state -- India; Mughal Empire -- Religion; Mughal Empire -- Politics and government; India -- Politics and government -- 997-1765.; Soufisme -- Inde -- Histoire; Islam et État -- Inde; Empire moghol -- Religion; Inde -- Politique et gouvernement -- 997-1765.; HISTORY / Asia / India & South Asia; Islam and politics; Islam and state; Politics and government; Religion; Sufism; India; India -- Mogul Empire; 997-1765; History